Exploring the challenges and possibilities of using learner-centered approach to teach in Nigeria Public Secondary Schools - Folashade, Aliu Juwerat (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Teaching is a universal human experience, a process of passing down information from generation to generation. Teaching is a deliberate activity done in a professional manner to bring a positive change in the learner; in order to teach well. The 21st-century student, as a digital native, has access to a mobile phone and can surf the internet, they do not want a teacher that will come to the class and still write what they have in their textbook and online, they want to be engaged academically, yet the Nigeria education, most especially secondary level are still rooted in using the traditional method of teaching in the classroom despite the outcry to shift the paradigm from teacher-centered approach to learner-centered approach, Therefore, this study aims to explore the challenges and possibilities of using the learner-centered approach to teach in Nigeria public secondary schools. The research is based on a qualitative research approach while a case study research design was used to explore the phenomenon under consideration, and constructivism theory was used as the theoretical foundation. Three research questions were raised to guide the conduct of this study, thematic coding was used to analyze the interviews where themes such as challenges (class size, attention problem, lack of teaching aids, financial constraints, student attitude, lack of teaching aids, time learner differences, unavailability of instructional material, environmental factors) and possibilities (class size reduction, government intervention, student positive attitude to learn, provision of infrastructure, teaching in area of specialization, teacher professional development) that emerged. The findings of the research show there are numerous possibilities indicating learner-centered approach can be put into practice in Nigeria despite all the challenges that teachers who have and are willing to use this approach encounter.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL) Vol 7 (2) (2023)
Keywords: Challenges; Possibilities; Teaching Methods; Learner-Centered; Teacher-Centered; Student-centered learning; Education -- Nigeria; Public schools -- Nigeria; Teaching -- Nigeria